Impact of Converging to IFRS on Key Financial Ratios with Reference to BSE Listed Firms - Amrutha, P.; Selvam, M.; Kathiravan, C. (International Journal of Psychosocial Rehabilitation, 2024)
This paper focused on providing prior evidence of the impact of accounting ratios resulted due to convergence to International Financial Reporting Standards (IFRS) in India. A graphical representation of its impact on the key performance indicators, after converging with IFRS, is shown in this paper. The accounting ratios presented using IGAAP and Ind AS on the date of convergence, 1st April 2016, were compared for the 79 sample companies using the Wilcoxon signed ranked test. Although earlier research explored the economic outcomes from International Financial Reporting Standard (IFRS) adoption, very few indicate the effects of IFRS adoption on key accounting ratios with reference to India. This study exhibits a significantly higher impact on the accounting ratios prepared under IFRS compared to those prepared under Indian GAAP.